Sosialisasi Pentingnya Masuk Keperguruan Tinggi : Studi pada Kelas IIS MAN 2 Oku Selatan - Mutmainah, Fitri Yanti (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose: This study investigates the process by which students in the Islamic Social Sciences (IIS) class of MAN 2 South OKU, Indonesia view higher education as important. It explores the factors and influences that shape students’ decisions about pursuing further studies after high school. Methodology/approach: A qualitative approach is likely to be employed, potentially utilizing interviews or focus group discussions with students, teachers, and possibly school officials. Result: This study is expected to reveal factors influencing students' decisions to pursue higher education, such as parental expectations, career aspirations, and exposure to university representatives. Additionally, it may identify methods used to instill the value of higher education within the IIS class, such as the school curriculum, guest lectures, or peer pressure. Contribution: This study can contribute to understanding how schools socialize students towards higher education, particularly within Islamic educational institutions in Indonesia. The findings can inform educators and policymakers on effective strategies to promote continued education among students in such contexts.